2015
DOI: 10.5336/medsci.2014-41309
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Brain Death: Experience of a Single Center

Abstract: Brain death is defined as the irreversible loss of consciousness and all functions of the brain stem. The accuracy and urgency of a diagnosis of brain death in children are highly important, because of the increasing rate of organ transplantation. Our objective was to describe the features of cases where "brain death" was diagnosed in the last five years. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : Demographical, clinical, electroencephalographic (EEG), Doppler ultrasonography and static single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…DI is an expected outcome in patients with brain death [17], and various studies have reported DI rates varying between 35-75 percent [11,14]. Similarly, the rate of DI was found to be 45 percent in the present study.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…DI is an expected outcome in patients with brain death [17], and various studies have reported DI rates varying between 35-75 percent [11,14]. Similarly, the rate of DI was found to be 45 percent in the present study.…”
Section: Discussionsupporting
confidence: 79%
“…In literature, the M/F ratio was found to be comparable in patients with confirmed brain death and age range was between 1-17 years [8,11]. In two different studies, the mean age was 7 and 7.8 years [12,13], while in the present study, the age range was 1-17 years and the mean age was 8.47±5.73 years.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…One study conducted by Gencpınar and her colleagues confirmed the pediatric organ donor rate in 2015 as 46%, while Yalındağ Öztürk et al [40] reported the rate of brain death as 1.1% and organ donor rate as 20%. [39] In this study, we diagnosed TBI-related brain death in six children (6.8%), of whom five became organ donors following family declarations. Although TBI-related brain death is only a small fraction of brain death etiology, recognizing the increase in donor trend at our center compared to previous years is inevitable.…”
Section: Discussionmentioning
confidence: 93%
“…Although TBI-related brain death is only a small fraction of brain death etiology, recognizing the increase in donor trend at our center compared to previous years is inevitable. [39] Positive physician-family communication and raising public awareness towards organ donation undeniably play an important role in the escalating trend. [41] Our study has some limitations: (i) retrospective nature of this study because of risks of potential bias, not allowing definite interpretations; (ii) a limited number of patients included owing to inclusion criteria for those admitted to PICU in 2-year period; (iii) evaluation of long-term cognitive functions on the study population was not possible; (iv) uncertainty about the time elapsed from the moment of trauma incident to PICU admission, which was quoted to be the most critical hours.…”
Section: Discussionmentioning
confidence: 99%